Melatonin ameliorates the adrenal and pancreatic alterations in streptozotocin-induced diabetic rats: Clinical, biochemical, and descriptive histopathological studies - Oyouni, Atif Abdulwahab A.; Al-Amer, Osama M.; Ali, Fatma Abo Zakaib; Altayar, Malik A.; Jalal, Mohammed M.; Albalawi, Rayan Salem M.; Abuderman, Abdulwahab Ali; Alsharif, Khalaf F.; AlZamzami, Waseem; Albrakati, Ashraf; Elmahallawy, Ehab Kotb (Frontiers in Veterinary Science, 2022)
Previous studies have demonstrated the beneficial effects of melatonin in diabetic rats. However, limited studies have been conducted on the potential effects of melatonin on the descriptive histopathological and morphometric findings in different compartments of the adrenal glands in diabetic animal models. In this study, using a streptozotocin (STZ)-induced diabetic rat model, we sought to examine histological alterations in the pancreas and adrenal glands and observe the effect of the administration of melatonin on the histopathology and morphology of the pancreas and the adrenal gland cortex and medulla that are altered by STZ-induced hyperglycemia. Rats were randomly assigned to four different groups: Group I, normal control; Group II, melatonin group (MT) (10 mg/kg/day); Group III, (diabetic STZ group), and Group IV, diabetic (STZ) + melatonin group (MT). Throughout the experiment, the animals' fasting blood sugar levels were measured. Blood was obtained to determine the animals' cumulative blood sugar levels after sacrification. For histological and morphometrical evaluations, the pancreatic and adrenal gland tissues were dissected and processed. Our results showed that diabetic rats receiving melatonin significantly (P < 0.05) improved their fasting blood sugar and cumulative blood sugar levels compared to the diabetic group not receiving melatonin. Furthermore, histopathological examinations of the pancreatic and adrenal tissues of the diabetic rats indicated the occurrence of severe histopathological and morphometric changes. Morphometric analysis of the adrenals indicated a significant increase (P < 0.05) in the thickness of the cortex zones [zona glomerulosa (ZG), zona fasciculata (ZF), and zona reticularis (ZR)] for the diabetic STZ group compared with other groups, and a significant decrease (P < 0.05) in the diameter of the in adrenal gland medullas in the diabetic STZ rats compared to the other groups. Furthermore, treatment with melatonin restored these changes in both the pancreatic and adrenal gland tissues and produced a significant (P < 0.05) improvement in the cortex and medulla thickness compared to the untreated diabetic rats. Overall, melatonin significantly reduced the hyperglycemic levels of glucose in diabetic rats and reversed the majority of histopathological alterations in the tissues of the pancreas and adrenals, demonstrating its anti-diabetic activity.